Eksplorasi Etnomatematika pada Desain Bangunan Masjid Raya Al-Mashun - Cyntia Suarni Arifin; Desmi Fitri Syahdani Br Sitepu; Mustika Nurbayeni; Nur Aisyah; Sazatul Asmal; Weni Sastika; Ella Andhany (Lembag, 2025)
Ethnomathematics knowledge towards mathematics learning. This type of research is exploratory research using an ethnographic approach. The results of the research show that there are ethno-mathematical aspects in the ornaments of the Al-Mashun Mosque, namely the dome, motifs on the entrance stairs, mosque pillars, motifs on the outer walls of the mosque, motifs on the floor, motifs on the dome, motifs on the entrance, and stairs. in the mosque. Where these ornaments can be linked to several geometric materials. First, flat shapes, such as squares, rectangles, right-angled trapezoids, isosceles trapezoids, triangles, rhombuses and octagons. Second, spatial shapes, such as tubes, balls, blocks and quadrilaterals. Third, regarding the concept of mathematical units.